ANALYSIS OF MATHEMATICAL CREATIVE THINKING ABILITY BASED ON SOLO'S TAXONOMY - Resvita Febrima; Ali Mahmudi (Universitas Labuhanbatu, 2026)
Purpose: This study aims to analyze high school students’ mathematical creative thinking skills based on the SOLO Taxonomy and to describe the characteristics of mathematical creative thinking at each SOLO level.Methodology: This study employed a mixed-methods design that integrated quantitative and qualitative approaches. The study participants consisted of 107 eleventh-grade students from four public high schools in Padang City, representing different school strata. The instrument used was a mathematical creative thinking test consisting of five open-ended questions, developed from indicators of mathematical creative thinking and the SOLO Taxonomy. Quantitative and qualitative analyses were conducted to describe students' mathematical creative thinking abilities and their characteristics at each SOLO level.Findings: The study indicates that students' mathematical creative thinking skills have not yet reached the very high category. Of the four aspects of creativity, flexibility received the highest percentage (84.37%), followed by elaboration (76.27%), fluency (75.61%), and originality (70.58%). Based on the SOLO Taxonomy, students were distributed across the prestructural, unistructural, multistructural, relational, and extended abstract levels, with the majority of students (82.32%) at the multistructural level. The research findings also indicate that the higher the SOLO level achieved by students, the higher their creative thinking skills in mathematics. This suggests that students at higher levels possess better abilities to connect concepts, generate diverse ideas, and build generalizations.Conclusion: This study contributes to mathematics education by presenting a comprehensive overview of students' mathematical creative thinking abilities at each SOLO level and demonstrating the relationship between the SOLO Taxonomy and these abilities. The findings of this study confirm that the SOLO Taxonomy can be utilized as a framework for identifying students' thinking levels and for designing HOTS-based learning and assessment strategies to enhance students’ mathematical creativity.